PENGARUH TINGKAT MODAL KERJA TERHADAP HARGA SAHAM PADA PERUSAHAAN OTOMOTIF & KOMPONEN YANG TERDAFTAR DI BEI PERIODE 2014 – 2018 - Hilda Ariska Br Lubis; Ihsan Effendi; Ahmad Prayudi (Universitas Medan Area, 2020)
This study aims to determine the effect of the level of working capital on stock prices on automotive companies components listed on the Indonesia Stock Exchange. This type of research is explanatory research, namely research that explains the relationship between existing variables. The method used is multiple panel linear regression analysis with the help of eviews program 10. The population in this study were all automotive companies components listed on the Indonesia Stock Exchange in 2014-2018, amounting to 13 companies. The sample in this study were 4 companies. The results showed that based on the F test, cash turnover, accounts receivable turnover and inventory turnover had a probability value of 0,000 0.05 and obtained a Ftable value of 3.24 and a Fcount value of 12,80464 which meant that Fcount Ftable in a simultaneous cash turnover, receivable receivables and inventory turnover affects the stock price. Determination coefficient value (R2) of 0.7884, so it can be concluded that 78.8484% of the stock price is influenced by cash turnover, accounts receivable turnover and inventory turnover and the remaining 21.16% is influenced by other variables not examined in this study.